A bibliometric analysis of leading universities in innovation research - Christian A. Cancino; José Maria Merigó; Freddy C. Coronado (Journal of Innovation & Knowledge (JIK), 2017)
The number of innovation studies with a management perspective has grown considerably over the last 25 years. This study identified the universities that are most productive and influential in innovation research. The leading innovation research journals were also studied individually to identify the most productive universities for each journal. Data from the Web of Science were analyzed. Studies that were published between 1989 and 2013 were filtered first by the keyword "innovation" and second by 18 management-related research areas. The results indicate that US universities are the most productive and influential because they account for the most publications with a high number of citations and high h-index. Following advances in the productivity of numerous European journals, however, universities from the UK and the Netherlands are the most involved in publishing in journals that specialize in innovation research.
Keywords: O30; O31; O32; O35; 650; Innovation; Bibliometrics; University analysis; Web of science